2002
DOI: 10.5935/0034-7167.20020100
|View full text |Cite
|
Sign up to set email alerts
|

REBEn: 70 ANOS NA CONSTRUÇÃO SOCIAL DO CONHECIMENTO DA ENFERMAGEM NO BRASIL

Abstract: A Enfermagem é um campo de atuação profissional implantada a partir da segunda década do século XX e consolidada, ao longo de cerca de oitenta anos, como resultado do trabalho competente, perseverante e dedicado de milhares de pessoas e instituições comprometidas com o desenvolvimento intelectual, político, ético e econômico-social do conjunto de profissionais e da prática de enfermagem, tendo em vista, a oferta de serviços de enfermagem de qualidade e acessível a todas as pessoas, grupos e classes sociais, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Only a third of puerperal women claim to receive information about breastfeeding during prenatal care, many do not know how to inform the recommended EBF time and a minority obtain guidance on milk storage and on the use of teats and pacifiers. Data from 2013 showed that 100% of mothers intended to perform EBF in a Baby Friendly Hospital Initiative in the city of São Paulo, however, only 34.1% managed to reach the child up to 180 days of life (SILVA, M. et al, 2018;SILVA, N., et al, 2014;ROCCI;FERNANDES, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Only a third of puerperal women claim to receive information about breastfeeding during prenatal care, many do not know how to inform the recommended EBF time and a minority obtain guidance on milk storage and on the use of teats and pacifiers. Data from 2013 showed that 100% of mothers intended to perform EBF in a Baby Friendly Hospital Initiative in the city of São Paulo, however, only 34.1% managed to reach the child up to 180 days of life (SILVA, M. et al, 2018;SILVA, N., et al, 2014;ROCCI;FERNANDES, 2014).…”
Section: Introductionmentioning
confidence: 99%